Joss App: Schedule Matching App to Set Up Realtime Group Activity Schedule - Rilo Pembudi, Eko Muhammad; Arfa, Muh. Ihsan Syaputra (International Journal of Management and Education in Human Development, 2021)
Communication technology today cannot be separated from aspects of human life. The development of various communication technology devices that are quite significant from each generation is influenced by increasing complex human demands and needs. Communication technology products that are widely used by society today are smartphones. Due to its practical nature, smartphones are inseparable devices in everyday life. More than 50% of internet users in Indonesia use the internet. The sophistication of smartphone technology really helps everyday human life both as a medium of communication, a medium for data exchange, a source of information, and a means of transacting in the business world. But sometimes humans also need to interact directly with other humans, as the human understanding in sociology says that humans are social beings who cannot live their lives individually. Meetings between individuals or between groups in person sometimes experience obstacles because each person's busyness is different. In fact, sometimes there are meetings that have to be canceled due to difficulties in scheduling the people we want to meet. One of the difficulties in matching schedules occurs because the methods used in scheduling and matching schedules are still conventional. In October 2020, the author conducted a survey on “The difficulty of making an appointment with someone” to 34 respondents, the results of the survey showed that more than 50% of respondents had difficulty meeting someone, this was due to various reasons, one of the reasons What respondents said most was the difficulty in matching schedules with friends. The results of the same survey also reveal that almost 100% of respondents still use conventional methods of recording their daily schedules. From the problems described above, an application is needed to assist the community in managing and matching schedules between individuals or groups.